The Perseverative Thinking Questionnaire in Patients with Persecutory Delusions. Issue 4 (24th August 2015) - Černis, Emma; Dunn, Graham; Startup, Helen; Kingdon, David; Wingham, Gail; Evans, Nicole; Lister, Rachel; Pugh, Katherine; Cordwell, Jacinta; Mander, Helen; Freeman, Daniel
Abstract : Background: Ruminative negative thinking has typically been considered as a factor maintaining common emotional disorders and has recently been shown to maintain persecutory delusions in psychosis. The Perseverative Thinking Questionnaire (PTQ) (Ehring et al., 2011 ) is a transdiagnostic measure of ruminative negative thinking that shows promise as a "content-free" measure of ruminative negative thinking. Aims: The PTQ has not previously been studied in a psychosis patient group. In this study we report for the first time on the psychometric properties of Ehring et al.'s PTQ in such a group. Method: The PTQ was completed by 142 patients with current persecutory delusions and 273 non-clinical participants. Participants also completed measures of worry and paranoia. A confirmatory factor analysis was performed on the clinical group's PTQ responses to assess the factor structure of the measure. Differences between groups were used to assess criterion reliability. Results: A three lower-order factor structure of the PTQ (core characteristics of ruminative negative thinking, perceived unproductiveness, and capturing mental capacity) was replicated in the clinical sample. Patients with persecutory delusions were shown to experience significantly higher levels of ruminative negative thinking on the PTQ than the general population sample. The PTQ demonstrated high internal reliability. Conclusions: This study did not include test-retest data, and did not compare the PTQ against a measure of depressive rumination but, nevertheless, lends support for the validity of the PTQ as a measure of negative ruminative thinking in patients with psychosis.